O Quaternário no Escudo Sul-Rio-Grandense: um Paleoambiente Lacustre em Encruzilhada do Sul, RS. - TOLEDO, FELIPE ANTONIO DE LIMA; COSTA, KAREN BADARACO (Pesquisas em Geociências, 1997)
Quaternary lacustrine deposits were identified and studied for the first time in a 1.2 m core test (PED-92/T-15) on the Precambrian Shield of Rio Grande do Sul at Encruzilhada do Sul. The area of the deposit is about one kilometer square. Sedimentologic and micropaleontologic study identified the following sequence: sand (base) → non laminated, silty black clay → slightly sandy/silty black clay → silty black clay with organic matter and some pebbles. Diatoms of the Order Pennales are the dominant microfossils. The sedimentary sequence shows that an initial shallow, sandy lake eutrophied and became filled with organic-rich clays.